Convergência de renda: uma análise para os estados nordestinos no perído de 1995-2009 - Gomes, Rafaela Rodrigues (2013)
This paper examines the hypothesis of GDP per capita convergence in the northeastern states, the period 1995-2009, with a focus on human capital. The reason to analyze the Northeast only and not all regions of Brazil is to retain the condition of homogeneity, necessary to analyze convergence issues. Using theories and models of economic growth, we tested the hypothesis of convergence ß- (absolute and conditional) convergence, and -o- during the period analyzed. Using Stata software version 12.1, the coefficients were estimated using panel data with fixed effects, whose main advantage is in capturing behavior changes of the indicators analyzed, obtaining more data, informative and efficient, which would not be possible with only data cross section or time series. The results pointed to the existence of convergence-o-, ß- and ß--absolute-conditional, obtaining, in the case of absolute convergence, growth rates well above those found in the empirical literature. Under the use of proxies of human capital, the conditional convergence proved apparently differentiated between samples considered, revealing the persistence of differences interstate.